Cell type-specific expression of JC virus early promoter is determined by positive and negative regulation. - Tada, H (1989)
We analyzed control sequences of the human papovavirus JC virus (JCV) to define the cis-acting elements that regulate specific expression of the viral early region genes in glial cells. Nuclear run-on transcription, S1 analysis, and chloramphenicol acetyltransferase enzyme activity in a transient transfection assay established that the cell type-specific expression of JCV early genes is determined at the transcriptional level. Using DNase footprinting analysis of nuclear proteins prepared from glial and nonglial cells, we located four regions within the JCV control sequences that specifically interacted with the proteins. In glial cells, all four domains contributed to the specific expression of a heterologous promoter, whereas in nonglial cells, two protein-binding regions showed no effect on basal transcriptional activity and the other two domains significantly downregulated transcription of the promoter. We conclude that cell type-specific transcription of the JCV early promoter is under both positive and negative regulation in eucaryotic cells.